Pacuan Kuda Sebagai Warisan Budaya: Studi Kualitatif Tentang Peran Dan Persepsi Masyarakat Di Arena Angin Laut Biru - Arisandi, Bobi (Kartika: Jurnal Studi Keislaman, 2025)
The horse racing tradition at Arena Angin Laut Biru, Sumbawa, represents a long-standing intangible cultural heritage that functions as a marker of local identity, a medium of social interaction, and a driver of community-based economic activities. Nevertheless, its sustainability is challenged by modernization, declining youth interest, limited government regulation, and ethical debates over child jockeys. This study seeks to analyze the socio-cultural roles of horse racing while exploring community perceptions of its continuity amid contemporary social changes. The research employed a qualitative case study approach. Data were collected through participatory observation, in-depth interviews, and documentation of visual and archival sources. Data were analyzed using Miles and Huberman’s interactive model, encompassing data reduction, data display, and conclusion drawing. Findings reveal that horse racing is more than a popular spectacle; it embodies local identity, reinforces social solidarity, serves as a medium for transmitting cultural and religious values, and stimulates local economic activities. Furthermore, the tradition holds strong potential to be developed into a community-based cultural tourism attraction. This study contributes to the broader literature on living heritage in Indonesia and offers practical implications for preservation strategies, including community involvement, digital promotion, child jockey protection regulations, and the integration of horse racing into sustainable cultural tourism development.